PENINGKATAN PERLINDUNGAN HUKUM TERHADAP PELAKU USAHA MIKRO KECIL DAN MENENGAH DI PROVINSI DKI JAKARTA - Saly, Jeane neltje; Yehezkiel, Raymond; Ramania, Hasya; a, Diana; Baramul, Christian Julius Ottofordtinatus; Putra, Muhammad Rangga Arya; Ariqah, Nailah (Peneliti.net, 2023)
MSMEs have a central role in the national economy, but the government contributes more and pays full attention to big businesses. So, this causes the need for legal protection for MSMEs. This study focuses on the discussion of how the legal protection efforts against the Micro, Small, and Medium Enterprises (UMKM) industry in Jakarta and how the concept of protecting MSMEs is based on an economic justice approach. The research method used in this study is a normative empirical legal research method, with descriptive-analytical research specifications for further data collection using literature studies sourced from primary, secondary, and tertiary legal materials for further qualitative analysis. The results of this study indicate that MSMEs as a small-scale industry still think that intellectual property protection is not important